Molecular characterization of cattle and sheep isolates of Echinococcus granulosus from Elazig province in Turkey and expression analysis of the non-coding RNAs, egr-miR-7, egr-miR-71 and egr-miR-96 - Irehan, Bunyamin; Celik, Figen; Koroglu, Ergun; Tektemur, Ahmet; Simsek, Sami (Academic Press Inc Elsevier Science, 2023)
Cystic Echinococcosis (CE) is a common zoonotic disease seen in human and animals worldwide, caused by the larval form of Echinococcus granulosus. In this study, E. granulosus s.l. species and haplotypes were determined in hydatid cysts isolated from cattle and sheep, and the expression levels of egr-miR-7, egr-miR-71 and egr-miR-96 miRNAs were compared in different cyst structures. A total of 82 (cattle, n = 41; sheep, n = 41) hydatid cyst isolates (germinal membranes and/or protoscoleces) were collected from a slaughterhouse in Elazig province of Turkey. After mt-CO1 gene sequences were made, 81 out of 82 hydatid cyst isolates were determined as E. granulosus s.s. (G1 and G3), while an isolate of cattle origin was determined as Echinococcus canadensis (G6/7). A total of 26 nucleotide polymorphisms and 29 haplotype groups were identified in the samples. miRNA expressions in germinal membranes of sterile cysts and germinal membrane and protoscoleces of fertile cysts were investigated by qRT-PCR and Real Time PCR analyses. It was determined that miRNAs were expressed at high levels in 79.31% of the 29 haplotype groups and at low levels in the remaining 10.34%. In 10 fertile samples of sheep origin, egr-miR-7, egr-miR-71 and egr-miR-96 miRNAs were found to be 44, 168, and 351-fold higher in expression, respectively, in the germinal membrane compared to the protoscoleces. Especially egr-miR-96 may have the potential to be used as biomarkers in the diagnosis of active CE.
Keywords: Echinococcus granulosus; Haplotype analysis; miRNA; Egr-miR-7; Egr-miR-71; Egr-miR-96